Forming future teachers' valuable and notional competence as the scientific and pedagogic problem - S. N. Kozachenko (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The aim of the article is the research of conceptual basis of work in forming future teachers' valuable and notional competence. The theoretical analysis of problems of future teachers' valuable and notional competence was performed. The result of the research is to define the matter of the valuable and notional competence, to classify its main elements, such as: personal, notional, behavioral and evaluative. The scientific approaches to the problem of forming future teachers' valuable and notorious competence, among which, the most productive are axiological, active, self-oriented, contextual and competency building ones, were systematized. General principles of work of future teachers' valuable and notorious competence are determined. This allowed to substantiate pedagogical conditions of forming valuable and notional competence of future teachers.